The Use of Think Pair and Share Technique in Teaching Reading to the Seventh Grade of Senior High School - Yulianingsih, Lia (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2017)
The study was conducted to determine  the use think-pair-share technique is effective in teaching descriptive reading that improved students’ achievement in reading comprehension. This objective is supported by Frank Lyman’s theory, “Think-pair-share is a learner centered and highly effective collaborative teaching strategy that is widely used in higher education”. That statement was proven and can be seen from the students activities during the implementation of think-pair-share in teaching learning activities. This study used quantitative method, and experimental with one group pre-test – post-test as the design. There were thirty five students from the seventh grade of SMPN 1 Palimanan Kabupaten Cirebon were used as the sample. In the experimental class, the writer used think-pair-share as the treatment, it has been done in three meetings. Pre-test and post-test was used to gain the data. There were ten question of essay students’ sheet was used as intruments of the test. The experiment class showed a significant reading comprehension, it shows that taccount is higher than ttable (18.13 taccount  2.032 ttable). Based on the reasult the writer concludes that use of think-pair-share technique in teaching descriptive reading is effective in improving students’ reading comprehension. Keyword   : Think-Pair-Share Technique, Descriptive Text, Teaching Reading Comprehension